Postinjury anxiety and social support among collegiate athletes: A comparison between orthopaedic injuries and concussions - Covassin, T.; Crutcher, B.; Bleecker, A.; Heiden, E. O.; Dailey, A.; Yang, J. (Journal of Athletic Training, 2015)
Context: When an athlete is injured, the primary focus of the sports medicine team is to treat the physical effects of the injury. However, many injured athletes experience negative psychological responses, including anxiety, regarding their injury.